(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg eSJMb GdMeO HfYeGFg aEf eYQaI GddZI GdJi hQO HgG NWGH Gddg MJi LeYgG fThGf QMeg Gddg ai cJGHg SGHbkG ZjQ dGMb SCdJi Cf GNJUQ eNJUQkG SejJg cJGH VjGA GdMdhe GdeNJUQ ef TeS GdYdhe s
(3BNQgG (B:s
(3hjLhR EKHGJ GdCda hGdgGA ai Gdhba afbhd jG GHf CeGg aEf hUdJ MPaJ GdgGA bGd (B: ( (3jG GHfI YeG dG Jdhei hGgLYi (B) (3Je GdcJGH s
(3GdeDda gh hdO UGMH TeS GdYdhes
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfG hcJHI GdUaMGJ GdChdi hGdCNjQI efgG HNW eNJdas
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GddZIs